REHABILITATION WITH THE APPLICATION OF THERAPEUTIC PHYSICAL CULTURE FOR PATIENTS AFTER CORONAVIRUS INFECTION AT THE OUTPATIENT STAGE - B., Aripova V.; Kh., Muminova N.; K., Mnazhov K. (Journal of Medical Genetics and Clinical Biology, 2024)
The article presents a review of scientific literature, clinical observations, containing data on the features of neurological manifestations and mental disorders, complications from the nervous system in a new coronavirus infection, illustrated with clinical examples. Neurological manifestations are not leading in the clinic for diseases caused by coronaviruses. However, the development of the nervous system is also possible with respiratory, sensory, motor, autonomic and other disorders of the central and peripheral nervous system. In addition, COVID-19 can worsen the course of already existing neurological diseases, therefore, this article provides basic recommendations for the management of certain groups of patients with nervous diseases. Given the earlier epidemics of other coronavirus infections, neurologists most often face cognitive and psycho-emotional disorders and other pathologies in the subsequent period. Therefore, it is important to choose the appropriate treatment and monitor the development of early and long-term consequences of neurological manifestations and complications of COVID-19 and then evaluate the effectiveness of effective individual rehabilitation programs for patients.